2013
DOI: 10.1111/pedi.12072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single autologous cord blood infusion on beta-cell and immune function in children with new onset type 1 diabetes: a non-randomized, controlled trial

Abstract: An autologous cord blood infusion does not change the natural course of metabolic and immune parameters after disease onset. However, the content of CD34+ cells in the stored blood sample might offer potential for improvement of future cell therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Two smaller studies have evaluated the effect of non-expanded autologous umbilical cord blood transfusions into children with recent onset T1D [70,71]. Although well tolerated, neither demonstrated an impact on decline in beta cell function, likely due to an insufficient number of Tregs or loss of function with long-term storage of the cells.…”
Section: Source Of Tregsmentioning
confidence: 99%
“…Two smaller studies have evaluated the effect of non-expanded autologous umbilical cord blood transfusions into children with recent onset T1D [70,71]. Although well tolerated, neither demonstrated an impact on decline in beta cell function, likely due to an insufficient number of Tregs or loss of function with long-term storage of the cells.…”
Section: Source Of Tregsmentioning
confidence: 99%
“…Infusion of autologous UCB failed to preserve C‐peptide, reduce insulin dose, and decrease HbA1c level; only a transient rise in CD4 + CD25 + T reg cells was observed 6 months after UCB infusion . Researchers in Germany also performed the same trial and obtained almost the same results in T1DM patients with a disease duration <1 year . However, it was shown that there was a significant correlation between the change in the area under the curve for C‐peptide concentrations from baseline to 6‐months an the number of CD34 + UCB cells infused, suggesting that expansion of UCB CD34 + cells may provide potential cell therapy for T1DM …”
Section: Autologous Ucb Cell Transplantation For T1dmmentioning
confidence: 94%
“…16,17 Researchers in Germany also performed the same trial and obtained almost the same results in T1DM patients with a disease duration <1 year. 18 However, it was shown that there was a significant correlation between the change in the area under the curve for C-peptide concentrations from baseline to 6-months an the number of CD34 + UCB cells infused, suggesting that expansion of UCB CD34 + cells may provide potential cell therapy for T1DM. 18 Because animal and clinical studies suggest that vitamin D and docosahexaenoic acid (DHA) may play a role in preventing and treating T1DM, 40,41 researchers conducted another open-label randomized study in which patients received combination therapy of autologous UCB infusion and 1 year of daily supplementation with vitamin D and DHA.…”
Section: Autologous Ucb Cell Transplantation For T1dmmentioning
confidence: 99%
See 1 more Smart Citation
“…CB is now stored in a growing number of banks, mainly as an immediately available and ethically acceptable source of hematopoietic stem cells [14]. Whole CB has also been assessed for therapy in some case studies of neurological disease [15], and in type 1 diabetes [16][17][18].…”
Section: Endocrine Carementioning
confidence: 99%